2010
DOI: 10.1074/jbc.m109.093138
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Arrangement of the Parathyroid Hormone Receptor and a Structural Mechanism for Ligand-induced Dissociation

Abstract: The parathyroid hormone receptor (PTH1R) is a class B G protein-coupled receptor that is activated by parathyroid hormone (PTH) and PTH-related protein (PTHrP). Little is known about the oligomeric state of the receptor and its regulation by hormone. The crystal structure of the ligand-free PTH1R extracellular domain (ECD) reveals an unexpected dimer in which the C-terminal segment of both ECD protomers forms an ␣-helix that mimics PTH/PTHrP by occupying the peptide binding groove of the opposing protomer. ECD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 59 publications
6
62
0
Order By: Relevance
“…For family B receptors, there is consistent evidence for homooligomerization, together with the potential for functionally important heterooligomerization (18)(19)(20)(21)(22)(23)(25)(26)(27). Within this theme, there is an emerging paradigm of behavior in which homodimerization of receptors occurs via a TM4/TM4 interface and that this interaction is required for optimal function of the receptor, generation of high-affinity agonist binding, and signaling via formation of cAMP (17,18,31); this paradigm is true also for the GLP-1R.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For family B receptors, there is consistent evidence for homooligomerization, together with the potential for functionally important heterooligomerization (18)(19)(20)(21)(22)(23)(25)(26)(27). Within this theme, there is an emerging paradigm of behavior in which homodimerization of receptors occurs via a TM4/TM4 interface and that this interaction is required for optimal function of the receptor, generation of high-affinity agonist binding, and signaling via formation of cAMP (17,18,31); this paradigm is true also for the GLP-1R.…”
Section: Discussionmentioning
confidence: 89%
“…For family B GPCRs, which encompass many therapeutically important peptide receptors, including those for glucagon, glucagon-like peptides 1 and 2 (GLP-1, GLP-2), parathyroid hormone, and calcitonin, there is consistent evidence for homodimerization (17)(18)(19)(20)(21)(22)(23)(24)(25). There is also emerging evidence for functionally significant heterodimerization (25)(26)(27).…”
mentioning
confidence: 99%
“…For family B GPCRs, homodimerisation has been shown to occur with the calcitonin receptor [149)], secretin receptor [150] and parathyroid receptor [151]. There is also interest in the development of allosteric agonists and whether they interact with a single receptor (in cis) or across dimers (in trans).…”
Section: The Glp-1r In Type 2 Diabetes Characterisation Of the Glp-1rmentioning
confidence: 99%
“…A large number of fluorescent ligands are available for GPCRs (Kuder and Kiec-Kononowicz 2008), but there will no doubt be receptors for which production of such ligands is challenging. It should be noted that in this type of experiment it is impossible to study dimers in the unliganded state, a condition which may be of particular significance when ligand binding can promote or inhibit dimer formation (Lukasiewicz et al Pioszak et al 2010). Finally, it may not be possible to study receptors expressed at low levels or cells which express multiple receptors for the same ligand.…”
Section: Fluorescent Ligands For Probing Gpcr Dimerisation In Native mentioning
confidence: 99%
“…A wholecell BRET approach with PTH1R fused to C-terminal luciferase or YFP revealed that PTH1R forms a constitutive dimer which is mediated by the ECD (Pioszak et al 2010). Addition of the agonist PTH disrupted the dimer, suggesting that monomers are the signalling unit.…”
Section: Effects Of Ligand Binding On Gpcr Dimerisationmentioning
confidence: 99%